Dental Pulp Stem Cell Mechanoresponsiveness: Effects of Mechanical Stimuli on Dental Pulp Stem Cell Behavior - Marrelli, Massimo; Codispoti, Bruna; Shelton, Richard M.; Scheven, Ben A.; Cooper, Paul R.; Tatullo, Marco; Paduano, Francesco (Frontiers in Physiology, 2018)
Dental pulp is known to be an accessible and important source of multipotent mesenchymal progenitor cells termed dental pulp stem cells (DPSCs). DPSCs can differentiate into odontoblast-like cells and maintain pulp homeostasis by the formation of new dentin which protects the underlying pulp. DPSCs similar to other MSCs reside in a niche, a complex microenvironment consisting of an extracellular matrix, other local cell types and biochemical stimuli that influence the decision between stem cell (SC) self-renewal and differentiation. In addition to biochemical factors, mechanical factors are increasingly recognized as key regulators in DPSC behaviour and function. Thus, microenvironments can significantly influence the role and differentiation of DPSCs through a combination of factors which are biochemical, biomechanical and biophysical in nature. Under in vitro conditions, it has been shown that DPSCs are sensitive to different types of force, such as uniaxial mechanical stretch, cyclic tensile strain, pulsating fluid flow, low-intensity pulsed ultrasound as well as being responsive to biomechanical cues presented in the form of micro- and nano-scale surface topographies. To understand how DPSCs sense and respond to the mechanics of their microenvironments, it is essential to determine how these cells convert mechanical and physical stimuli into function, including lineage specification. This review therefore covers some aspects of DPSC mechanoresponsivity with an emphasis on the factors that influence their behaviour. An in-depth understanding of the physical environment that influence DPSC fate is necessary to improve the outcome of their therapeutic application for tissue regeneration.